Deregulatory takings and the regulatory contract : the competitive transformation of network industries in the United States / J. Gregory Sidak, Daniel F. Spulber. - Sidak, J. Gregory; Spulber, Daniel F. (Cambridge University Press, 1997)
This 1998 book addresses deregulatory policies that threaten to reduce or destroy the value of private property in network industries without any accompanying payment of just compensation, policies that are termed 'deregulatory takings'. The authors further consider the problem of renegotiation of the regulatory contract, which changes the terms and conditions of operation of utility companies. They argue that constitutional protections of private property from takings, as well as efficient remedies for contractual breach, provide the proper foundation for the competitive transformation of the network industries. The benefits of competition do not stem from government regulations that redistribute income from utility investors to customers, nor do such benefits stem from regulatory policies for network access that promote free riding on incumbent facilities by entrants. Such actions represent a new version of increased regulation, not deregulation.